Implications of Rapid Urban Expansion on Rural Land Use in Damaturu, Yobe State, Nigeria (2014)
The implications of rapidly expanding cities on rural hinterlands have been documented in the literature. However, such implications are understudied in developing nations including Nigeria. This study, therefore, investigated the implications of rapid expansion of Damaturu, Yobe State, the fastest expanding state capital in northern Nigeria on rural land use pattern from 1986 to 2009. Environmental resource carrying capacity and distance decay effect provided the analytical framework. Survey research design was employed, while sampling elements were clustered and randomly sampled. The Local Government Areas surrounding Damaturu city (Damaturu, Tarmuwa, Fune, Gujba and Kaga) were purposively selected while the four major roads linking Damaturu with the neighbouring states provided the basis for subdividing the study area into four zones. Settlements in each zone were grouped into three, based on distance from Damaturu (<15km; 15-30km; >30km). Two settlements were randomly selected from each group. Two sets of questionnaire were administered to the population (household heads and firewood merchants/local building resource merchants) to elicit information on socio-demographic characteristics (population, age, sex, income), perception of urban expansion, implications on rural land use changes, rural resources depletion and severity index. There were 8,180 residential buildings in the selected settlements, 409 (5.0%) were randomly selected from which household heads were sampled. Similarly, 10.0% of 351 firewood merchants, 652 local building resource (soil, sand, gravel) merchants were randomly sampled. Imagery data collected were analysed using appropriate software. Pre- and post-classification comparison methods were employed to measure the changes of bare surface land, built-up area, tree-cover area and water-bodies. Data were analyzed using descriptive statistics, weighted opinion assessment and Severity Index (SI) at p<0.05. Over ninety percent of respondents were males; mean age was 35.27±12.98 years while mean annual Income (in thousands) was 34.75±23.44. Population increased from 363,131 (1986) to 770,550 (2009). Bare land increased from 435.1ha (1986), 1,397.3ha (1999) to 2,936.2ha (2009). Built-up land increased from 398.6ha (1986), 2,045.9ha (1999) to 3,078.3ha (2009). Tree cover land decreased from 8,420.6ha (1986), 4,597.8ha (1999) to 2,642.9ha (2009). Water bodies decreased from 256.1ha (1986), 130.6ha (1999), to 72.0ha (2009). Average percentage of SI was 62.5%; SI decreased as distance increased 97.6% (<15km), 68.5% (15–30km) and 14.3% (>30km), while mean SI was 2.16 (very severe). The implications (rapid rural land use conversion, fast depletion of local building resources, decreasing water bodies) were perceived by 85.9% of the respondents as being negative. Fire-wood merchants viewed the expansion as negative because they expended more energy and cover longer distances for same quantity of resource. Local building resource merchants viewed increasing distance and rural degradation as negative, but made more sales to physical developers. Coping strategies of the household respondents included relocation of farm sites (78.0%), intensive agriculture (14.0%) and land conservation (8.0%). Fire-wood and local building resource merchants underwent longer distances for resources. Rapid rural land use conversion and rural resource depletion were viewed as negative implications of Damaturu expansion. Therefore, there is the need to evolve strategies to manage these negative implications on rural land use and resources.